Antistreptolysin O, rheumatoid factor and C-reactive protein determination in patients with recurrent oral ulcer. - (:unkn) unknown (My University, 1996)
Recurrent oral ulcer (ROU) is a common disease whose the etiologic factors have not yet been identified. Although the autoimmune mechanism due to streptococcal antigens may be involved in this disease, serum immunoglobulins are reported to be higher than normal controls in various phases of ROU. Oral ulcers are one of the criteria in the diagnosis of some systemic diseases such as Wegener's granulomatosis, Behçet's syndrome, suppurative arthritis, Reiter's syndrome and neutropenias. Any patient with recurring oral ulcers should be evaluated medically for the possible presence or future development of serious systemic diseases. In this study of the 58% of the ROU patients who had positive ASO values, only one female patient had a moderate increase: ++ASO(= 400 IU), the rest had a slight increase: +ASO(= 200 IU). In the control group only 3 female subjects had +ASO (= 200 IU). The aim of this study was to determine whether there is any relationship between ROU and rheumatoid arthritis. Patients with ROU were examined for antistreptolysin O, rheumatoid factor and C-reactive protein and compared to healthy controls.